1986
DOI: 10.1002/eji.1830160724
|View full text |Cite
|
Sign up to set email alerts
|

myo‐Inositol reverses Li+‐induced inhibition of phosphoinositide turnover and ornithine decarboxylase induction during early lymphocyte activation

Abstract: One of the earliest detectable responses by T lymphocytes in vitro to various mitogenic ligands is the rapid induction of ornithine decarboxylase (ODC) activity (Scott et al., Eur. J. Immunol. 1985. 15: 783). This early activation is measurable within minutes after the addition of the mitogen. The T cell mitogen concanavalin A also induces rapid breakdown of phosphoinositides in T lymphocytes. The inositol phosphates formed are recycled and used in synthesis of new phosphoinositides. Li+ interrupts this cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…We have earlier shown that an intact inositol metabolism is obligatory for the early activation of ODC (Mustelin et al, 1986). Here we show that the rapid ODC activation is inducible by nonhydrolysable GTP analogues, suggesting that a G-protein is an important link in the transduction of mitogenic signals.…”
Section: Introductionsupporting
confidence: 50%
“…We have earlier shown that an intact inositol metabolism is obligatory for the early activation of ODC (Mustelin et al, 1986). Here we show that the rapid ODC activation is inducible by nonhydrolysable GTP analogues, suggesting that a G-protein is an important link in the transduction of mitogenic signals.…”
Section: Introductionsupporting
confidence: 50%
“…We also examined the possibility that the effect of Li' on tubulin was related to its known interference with phospholipidmediated events via inhibition of myo-inositol l-phosphatase, resulting in the depletion of myo-inositol (Hallcher and Sherman, 1980;Berridge, 1984). Such effects can be mitigated by excess exogenous myo-inositol (Mustelin et al, 1986;Forer and Sillers, 1987;Busa and Gimlich, 1989). However, addition of 0.0 I -1 mM myo-inositol concurrently with Li' did not attenuate the Li+-induced decrease in radiolabeled tubulin levels.…”
Section: Resultsmentioning
confidence: 99%
“…One possible mode of action is interference by Li+ with inositol lipid turnover (Berridge, 1984) due to inhibition of phosphatidylinositol resynthesis (Hallcher and Sherman, 1980). Some of these consequences can be mitigated by the addition of excess exogenous myu-inositol (Mustelin et al, 1986;Forer and Sillers, 1987;Busa and Gimlich, 1989). On the other hand, if reduction in cyclic AMP levels (Zohar et a]., (lanes 2-6).…”
Section: Inhibition Of Neurofilament-m Phosphor Yla Tionmentioning
confidence: 99%